Glial fibrillary acidic protein as a prognostic marker of acute ischemic stroke. (October 2018) - Liu, G; Geng, J
Background: We investigated the association between serum levels of glial fibrillary acidic protein (GFAP) and stroke functional outcomes in a cohort of 286 patients with acute ischemic stroke (AIS). Methods: We prospectively studied 286 patients with AIS who were admitted within 24 h after the onset of symptoms. Serum levels of GFAP and National Institutes of Health Stroke Scale (NIHSS) were measured at admission. The primary end point was stroke functional outcome among 1-year after stroke onset. We used logistic regression models to assess the relationship between GFAP levels and stroke outcomes. Results: The GFAP level was obtained with a median value of 0.18 (interquartile ranges (IQRs): 0.09–0.28) ng/ml. In multivariable models adjusted for age, gender, and other risk factors, GFAP levels were associated with an increased risk of a NIHSS>6 (odds ratio (OR) = 1.55; 95% confidence interval (CI): 1.16–1.89; p = 0.012). The poor outcome distribution across the GFAP quartiles ranged between 12.7% (first quartile) and 70.4% (fourth quartile). After adjusting for other established risk factors, in multivariate models comparing the Q3 and Q 4 quartiles against the Q1 of the GFAP, the levels of GFAP were associated with poor outcome, and the adjusted risk of poor outcome increased by 211% (3.11[1.80–5.05], p < 0.001) and 522% (6.22[2.98–11.83], p < 0.001), respectively. Interestingly, GFAP improved the ability of NIHSS score to diagnose poor outcomes (area under the curve [AUC] of the combined model 0.82; 95% CI: 0.77–0.88; p = 0.02). Conclusion: GFAP levels are a novel and complementary biomarker to predict functional outcome 1 year after AIS